Rancang Bangun Tempat Sampah Pintar Berbasis Arduino Uno: Array - Sirait, Ricoplyando; Lubis, Imran (Universitas Harapan Medan, 2021)
The trash can is a container that can temporarily accommodate trash. Arduino uno-based smart trash can which includes an LCD sensor as a medium for displaying text in the trash. The PIR sensor functions as a motion detector for human presence, and the Green LED for notification of human presence in the trash, the Red LED for notification of full trash cans, and the Servo motor is used as a tool for opening and closing, and the ultrasonic sensor for detecting the volume of waste, and the buzzer as a tool for opening and closing. beep notification, if the pir sensor reads the presence of a person, if the volume of trash has entered 17cm distance that the Red LED will be High.